HOLMES St. FORENSIC LAB & EDUCATION CENTER (IDEA OF INTERIORITY THROUGH THE TRAIL OBSERVATION) - Rahmania Alaydrus (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2018)
Humans are the most important thing in a space experience. Two important aspects of public space are the feelings of comfort and discomfort. That comfort or discomfort kind of feeling in the public space, are obviously inseparable from the acts of crime. Through such approaches, I undertake this studies and a research for design, to identify the sequence of trails autopoietic processes, holistically, when human come up against their discomfort, and in their existential space. So, that specific and particular boundary from the trail will come up as identity. Identity of the past turns out into such an idea to be designed. When the segments are legible as segment-by-segment, the processes will be holistically identified as a whole story. When the presence of a trail becomes a boundary, therein the trail will appear as the interiority.